Response to Selection for Birth Weight in Priangan Sheep (Case Study on a Local Farm in Nenggeng Village, Darangdan Sub-District, Purwakarta Regency) - -, AI NURFARIDAH; Sari Suryanah; Syifa Nurjannah; Wahyu Suradi Pranata (UNIVERSITAS ISLAM LAMONGAN, 2025)
This study aims to determine the response to selection based on variations in selection intensity for birth weight in Priangan sheep. The study was conducted at a local farm in Nenggeng Village, Darangdan Sub-District, Purwakarta Regency, using a case study approach. The data analyzed were derived from the recorded birth weights of 108 lambs, which were the progeny of 6 rams and 36 ewes. Data analysis used descriptive statistics and analysis of variance (ANOVA). The response to selection was calculated based on standard deviation, heritability, and selection intensity. The most optimal selection intensity was achieved with the use of 0.44% (1 male lamb) and 4.11% (10 female lambs). The results of the analysis indicated that the response to selection was 0.138 kg. If selection is applied to the current generation, the birth weight of the next generation is expected to increase from 2.17 kg to 2.308 kg.